2014
DOI: 10.1016/j.ijrefrig.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical comparison of low GWP alternatives for different refrigeration configurations taking R404A as baseline

Abstract: Six refrigerants are evaluated as low GWP replacements for R404A using different configurations, including two-stage system architectures. These refrigerants are selected according to similar characteristics to R404A, and they are the mid-term alternatives R407A and R407F, and the long-term alternatives: L40 and DR-7 (with very low GWP and low flammability), N40 and DR-33 (with low GWP and no flammability). In order to have a complete comparison range, various operating conditions are considered, covering low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 12 publications
1
25
0
3
Order By: Relevance
“…The evaporating pressure is defined considering glide effects on heat exchangers, Eq. (1) is applied to correct R450A and R448A evaporating pressure [15,22].…”
Section: Tests Performedmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaporating pressure is defined considering glide effects on heat exchangers, Eq. (1) is applied to correct R450A and R448A evaporating pressure [15,22].…”
Section: Tests Performedmentioning
confidence: 99%
“…As happens for R450A, this HFO/HFC mixture also presents good performance. Mota-Babiloni et al [22] studied theoretically six R404A alternatives in four vapour compression configurations, obtaining high efficiency simulating with R448A. Yana Motta [23], using a 2.2 kW semi-hermetic condensing unit with evaporator for walk-in freezer/cooler, show that R448A matches the capacity of R404A with 6% higher efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…High-GWP refrigerant R404A (GWP = 3260) as medium and low temperature refrigerant is widely used in the CVRC based commercial refrigeration. It needs to be gradually replaced by low-GWP refrigerants, such as R290 [28,29]. Therefore, in this study, the refrigerants R404A and possible alternative R290 used in small low-temperature cabinet freezers are selected as examples to analyze the performance of ESVRC cycle [30].…”
Section: Cycle Performance Analysesmentioning
confidence: 99%
“…Ln et al [27] found that the SEER and SCOP of R32 and mixing refrigerant R446A were higher than R410A by 8% and 1% in a residential heat pump system. A comparison of R404A with six low-GWP mixing refrigerants including mid-term alternatives R407A and R407F and long-term alternatives L40, DR-7, N40 and DR-33 was conducted by Mota-Babiloni et al [28] in terms of cooling capacity, volumetric flow rate and COP, and conclusions were given that the most efficient alternatives were the low-flammable refrigerants L40 and DR-7 considering two-stage and diverse operating conditions. Devecioglu [29] evaluated seasonal efficiency of four new low-GWP mixing refrigerants including R446A, R447A, R452B and R454B whose GWP values were lower than 750 and concluded that R452B has the most suitable SCOP among the alternative refrigerants.…”
Section: Introductionmentioning
confidence: 99%